Immunotherapies and immunomodulatory approaches in clinical trials - a mini review - Mohd. Iqbal Yatoo; Zeenat Hamid; Izhar Rather; Qurat Ul Ain Nazir; Riyaz Ahmed Bhat; Abrar Ul Haq; Suhail Nabi Magray; Zulfqar Haq; Ranjit Sah; Ruchi Tiwari; SenthilKumar Natesan; Muhammad Bilal; et al. (Taylor & Francis Group, 2021)
The coronavirus disease (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has created havoc worldwide. Due to the non-availability of any vaccine or drugs against COVID-19, immunotherapies involving convalescent plasma, immunoglobulins, antibodies (monoclonal or polyclonal), and the use of immunomodulatory agents to enhance immunity are valuable alternative options. Cell-based therapies including natural killer cells, T cells, stem cells along with cytokines and toll-like receptors (TLRs) based therapies are also being exploited potentially against COVID-19. Future research need to strengthen the field of developing effective immunotherapeutics and immunomodulators with a thrust of providing appropriate, affordable, convenient, and cost-effective prophylactic and treatment regimens to combat global COVID-19 crisis that has led to a state of medical emergency enforcing entire countries of the world to devote their research infrastructure and manpower in tackling this pandemic.